"Adjuvant Surgery" in the Treatment of Metastatic Gastrointestinal Stromal Tumor's: a New Concept - Valadão, Marcus (2009)
Recent progress in gastrointestinal stromal tumor's (GIST) treatment was responsible for changing GIST's natural history. Knowlegde acquirement on molecular mechanism-based systemic therapy gave rise to the development of targeted antineoplastic drugs capable of reaching outcomes that had never been reached before. The introduction of imatinib in the clinical practice not only changed GIST patients´ survival, but also shifted paradigms. However, although imatinib has been considered the standard treatment of metastatic GIST, surgeon's role in this setting is being investigated. There is some evidence that surgery after imatinib treatment would benefit selected patients with metastatic disease. Therefore, a new concept has developed: "adjuvant surgery" as a new strategy to optimize treatment outcome in GIST metastatic scenario.